2007
DOI: 10.1523/jneurosci.3647-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reliably Detects Experimental Traumatic Axonal Injury and Indicates Approximate Time of Injury

Abstract: Traumatic axonal injury (TAI) may contribute greatly to neurological impairments after traumatic brain injury, but it is difficult to assess with conventional imaging. We quantitatively compared diffusion tensor imaging (DTI) signal abnormalities with histological and electron microscopic characteristics of pericontusional TAI in a mouse model. Two DTI parameters, relative anisotropy and axial diffusivity, were significantly reduced 6 h to 4 d after trauma, corresponding to relatively isolated axonal injury. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
339
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(381 citation statements)
references
References 48 publications
36
339
6
Order By: Relevance
“…Specifically, the repeated mTBI group displayed significantly lower RD values in these regions at Day 7 as compared to Day 1 postinjury. RD is often associated with myelin pathology and edema following trauma to the brain 53, 54. Although no differences were observed between sham and injured animals following repeat ACHI, decreasing RD values in a time dependent fashion may be indicative of injury progression.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, the repeated mTBI group displayed significantly lower RD values in these regions at Day 7 as compared to Day 1 postinjury. RD is often associated with myelin pathology and edema following trauma to the brain 53, 54. Although no differences were observed between sham and injured animals following repeat ACHI, decreasing RD values in a time dependent fashion may be indicative of injury progression.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, several recent studies using advanced neuroimaging techniques, such as diffusion tensor imaging (DTI), have elucidated changes in the white matter of mTBI patients (Bazarian et al, 2007;Huang et al, 2009;Inglese et al, 2005;Messe et al, 2010;Wilde et al, 2008). These human studies have been supported by evidence in rodent models of TBI that the signal changes seen with DTI correspond with axonal pathology (Mac Donald et al, 2007). Therefore, the current data demonstrate the potential utility of the swine mTBI model of head rotational acceleration to further these investigations by providing direct comparisons of the distribution of axonal pathology with signal changes found with advanced neuroimaging techniques, an effort that is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…MacDonald et al [20] used a mouse brain injury model and showed that relative anisotropy and axial diffusivity were reduced by 6 h to 4 days after trauma, corresponding to axonal injury, while 1-4 weeks after trauma, relative anisotropy remained decreased, whereas radial diffusivity increased, corresponding to demyelination, edema, and persistent axonal injury. Previous studies of ADC values in central nerve lesions such as spinal cord injury and multiple sclerosis and peripheral nerve compression such as found in carpal tunnel syndrome are controversial [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that DWI is useful for the evaluation and diagnosis of lesions such as multiple sclerosis [15,16] and peripheral nerve compression disorders such as carpal tunnel syndrome [17][18][19], using diffusion values such as ADC. An increase in the mean diffusivity (ADC) values was observed in injured nerves with demyelination [15,16,19,20]. Imaging of the spinal cord is challenging because of technical limitations such as the relatively small size of the cord, susceptibility artifacts because of tissue-bone interfaces, and the motion artifacts arising from respiratory activity [21].…”
Section: Introductionmentioning
confidence: 99%